Machine Learning-Based Systems for the Anticipation of Adverse Events After Pediatric Cardiac Surgery - Garcia-Canadilla, Patricia; Isabel-Roquero, Alba; Aurensanz-Clemente, Esther; Valls-Esteve, Arnau; Miguel, Francesca Aina; Ormazabal, Daniel; Llanos, Floren; Sanchez-de-Toledo, Joan (Frontiers in Pediatrics, 2022)
Pediatric congenital heart disease (CHD) patients are at higher risk of postoperative complications and clinical deterioration either due to their underlying pathology or due to the cardiac surgery, contributing significantly to mortality, morbidity, hospital and family costs, and poor quality of life. In current clinical practice, clinical deterioration is detected, in most of the cases, when it has already occurred. Several early warning scores (EWS) have been proposed to assess children at risk of clinical deterioration using vital signs and risk indicators, in order to intervene in a timely manner to reduce the impact of deterioration and risk of death among children. However, EWS are based on measurements performed at a single time point without incorporating trends nor providing information about patient’s risk trajectory. Moreover, some of these measurements rely on subjective assessment making them susceptible to different interpretations. All these limitations could explain why the implementation of EWS in high-resource settings failed to show a significant decrease in hospital mortality. By means of machine learning (ML) based algorithms we could integrate heterogeneous and complex data to predict patient’s risk of deterioration. In this perspective article, we provide a brief overview of the potential of ML technologies to improve the identification of pediatric CHD patients at high-risk for clinical deterioration after cardiac surgery, and present the CORTEX traffic light, a ML-based predictive system that Sant Joan de Déu Barcelona Children’s Hospital is implementing, as an illustration of the application of an ML-based risk stratification system in a relevant hospital setting.